Regulating the geographies of market making: offshore renminbi markets in London's international financial district - Hall, Sarah (Wiley, 2017)
In this paper, I develop a sympathetic critique of cultural economy approaches to market making, arguing that the spatial imaginations deployed in this work remain comparatively limited. Drawing on the emerging dialogue between cultural economy and heterodox political economy approaches to money and finance, the paper argues that a focus on regulation provides a valuable way of developing new understandings of the geographies of market making beyond cultural economy’s extant reading of space as context, particularly in the form of the financial trading room. Drawing on an original case study of the marking of offshore renminbi markets in London’s financial district, the analysis conceptualises regulation as both a hitherto overlooked relational component of market making and as a set of practices that co-constitute the territoriality of markets. I demonstrate how regulatory changes made in Beijing and London are important in understanding both the growth and potential limitations of London as an offshore renminbi centre. This has significant implications empirically, for the wider project of renminbi internationalisation and theoretically, in terms of understanding the geographies of market making.